Posthuman Mimesis II - Connections: A Dialogue between Nidesh Lawtoo and Katherine Hayles - Hayles, Katherine; Lawtoo, Nidesh (Journal of Posthumanism, 2022)
In this dialogue Katherine Hayles and Nidesh Lawtoo join forces to cast light on the central role of embodied mimesis in the emergence of the posthuman subject. From Platonic abstraction to Turing’s imitation game, hypermimetic conspiracy theories to contagious processes of affective contagion that go viral online before infecting subjects online to the Covid-19 pandemic crisis and microbiomimesis, the ancient concept of mimesis turns out to be, for better and worse, consciously and above all, unconsciously, inscribed in the human and nonhuman contagious processes that give birth to posthuman subjectivity.